Menggali Potensi Ekonomi Kreatif sebagai Sarana Pendukung Desa Wisata - Diyah Sukanti Cahyaningsih; Tonny Suhartono; Sri Widayati (University of Merdeka Malang, 2021)
Creative economy development in tourist villages is very important. In supporting the existence of a tourist village, homestays and special food souvenirs are the carrying capacity. Study of economic benefits is needed to strengthen the motivation of citizens in developing this creative economy. This Homestay service aims to provide a new source of income for the family. The Community Service Team organizes activities in several stages by prioritizing citizen participation. The service method used is the Community Based Development or Participatory Approach. This method is used to ensure the commitment of citizens to this economic empowerment program. With the participation of residents who are the basis of this program, it is believed that the program will continue after the mentoring period ends. The result of this dedication is the first, the arrangement of the house into a homestay with the category of